PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA MANAJERIAL - Utaminingsih, Audri (2014)
The purposes of this research are to know how Budget arrangement participation and the uncertainty of environment influences simultaneously toward managerial performance at PT. Krakatau Steel, to know how budget arrangement participation influences partially toward managerial performance at PT. Krakatau Steel and to know how the uncertainty of environment influences partially toward managerial performance at PT. Krakatau Steel. The research method used here is descriptive analytical. The research analysis units are mid-level manager and low-level manager (superintendent) on six departments of PT. Krakatau Steel. The data used are primary data and secondary data. The sampling technique is using saturated sampling. The sample obtained is fifty respondents. Statistical analysis used is multiple regression analysis. The conclusions of this research are: first, budged arrangement participation and the uncertainty of environment simultaneously have positive influence toward managerial performance. Second, budget arrangement participation partially has positive influence toward managerial performance. Third, the uncertainty of environment partially has positive influence toward managerial performance.